Radiosensitizing Effects of Lithium Ascorbate on Normal and Tumor Lymphoid Cells under X-ray Irradiation; Current Bioactive Compounds; Vol. 19- iss. 8 - Tretyakova (Tretjyakova) M. S. Maria Sergeevna; Brazovsky (Brazovskii) K. S. Konstantin Stanislavovich; Artamonov A. A. Anton Anatoljevich; Stuchebrov S. G. Sergey Gennadevich; Gogolev A. S. Aleksey Sergeevich; Larkina M. S. Mariya Sergeevna; Sukhikh E. S. Evgeniya Sergeevna; Plotnikov E. V. Evgeny Vladimirovich (2023, 2023)
The study aimed to assess the radiosensitizing effect of lithium ascorbate on tumor cells.